The relationship between employee individual, job and organizational characteristics with job satisfaction, organizational commitment and propensity to leave in the hotel industry in Tehran, Iran / Leila Radmand - Radmand, Leila (2011)
Operational employees play a pivotal role in delivering superior service quality to customers or converting aggrieved customers into satisfied and loyal ones. However, high workforce turnover rate, especially on operational level employees has been one of the most pressing issues of the global hotel industry. Managing staff turnover to improve retention can lead to better recruitment, lower costs, improved morale and a better knowledge base. Turnover fluctuates with economic cycles and during a recession, for example, often falls. This may disguise underlying problems (such as dissatisfied staff or lack of new talent), so it is important to manage the underlying factors relating to turnover, even though turnover itself may not always be a problem. The general objective of the study is to examine the predictors of hotel staff propensity to leave; and the mediating role of job satisfaction and organizational commitment and also individual characteristics (self-esteem and emotional intelligence), job characteristics (role conflict, role ambiguity and work overload) and organizational characteristics (perceived career advancement, empowerment and leader-staff relationship). Specifically it aims to examine the relationship between the research variables; whether job satisfaction and organizational commitment mediate the effect of independent variables such as (individual, job and organizational characteristics) on the dependent variable (propensity to leave). The sample size was 411 hotel employees in Tehran, Iran. The data analyses were conducted by a process of multivariate analysis using structural equation modelling (SEM) and AMOS (Analysis of Moment Structures) software package Version 17. There are seven parts in the findings which showed the relationship between the study variables and the role of the mediating variables. In the first part, findings show that self-esteem, role ambiguity, work overload, perceived career advancement and perceived empowerment effect job satisfaction. In the second part, findings show that just perceived leader-staff relationship effects organizational commitment. In the third part, findings show that perceived career advancement effects propensity to leave. In the fourth part, findings show that organizational commitment is related to propensity to leave. In the fifth part, findings show that job satisfaction effects organizational commitment. In the sixth part, findings show that job satisfaction mediates the effect of emotional intelligence, role ambiguity, role conflict, perceived career advancement and perceived empowerment on propensity to leave. In the final part, findings show that organizational commitment mediates the effect of role ambiguity, perceived career advancement and perceived empowerment on propensity to leave.